Literasi Informasi dalam Isu Kebebasan Pers: Tantangan perpustakaan dalam Menangkal Disinformasi di Masyarakat - Ramadani, Nurhamidah; Rodiah, Ita (Librarium: Library and Information Science Journal, 2025)
The aim of this research is to determine the function of libraries in increasing knowledge about information, overcoming the problem of disinformation in society, and ensuring healthy press freedom. It is hoped that this will be created with a collaborative approach between libraries, media and the community. The research method used is literature study. The research results show that libraries have a responsibility to educate the public to think critically and evaluate information correctly as institutions that can be trusted to provide access to information. Among the problems faced are the large number of fake news spreading through digital media, a lack of awareness of the importance of trusted sources, and the limitations of certain community groups in gaining access to technology. Therefore, libraries must use the latest technology, develop educational programs on relevant information literacy, and collaborate with other institutions to strengthen efforts to combat disinformation.